Race and pedagogy : creating collaborative spaces for teacher transformations - Adams, Susan R.; Buffington-Adams, Jamie (Race and education in the twenty-first century., 2016)
Race and Pedagogy identifies persistent, institutional racism as the cause of the lower rates of high school graduation among African Americans, Hispanics, and Native Americans in the United States. Adams and Buffington-Adams provide a retrospective look at their own and other teachers' efforts to acknowledge the limitations of their own cultural lenses in order to identify, examine, and fix the failings of the current educational system."--